The Analysis of Asymetric Dimethylarginine and Homocysteine in Patients with Chronic Kidney Disease - Tetty Hendrawati; Syakib Bakri; Mansyur Arif (The Indonesian Biomedical Journal, 2009)
BACKGROUND: Asymmetric dimethylarginine (ADMA) is a competitive inhibitor of nitric oxide synthase (NOS). ADMA reduces NO synthesis when its concentration elevates. ADMA is a novel risk factor for cardiovascular disease. Plasma ADMA accumulates in patients with endstage renal disease, due to reduced renal clearance. Hyperhomocysteinemia is often found in patients with chronic kidney disease (CKD). Homocysteine may cause ADMA to accumulate; however, the mechanism by which ADMA level elevates in hyperhomocysteinemia is still unclear. Objective of this study was to analyze the concentrations of homocysteine and ADMA and to assess the correlation between homocysteine and ADMA concentrations with the severity of chronic kidney disease.METHODS: This was a cross-sectional study on 75 patients with CKD, comprising men and women aged 40-70 years. Assessments were done on the concentrations of creatinine, homocysteine, ADMA, fasting blood glucose, cholesterol HDL and triglyceride.RESULTS: In later stage of CKD there was significantly higher tHcy concentration as compared with the earlier stage of CKD (p=0.0000). In CKD stage 2 to 4 there was a tendency for ADMA concentration to increase to a significant average (p=0.210), but ADMA concentration was lower at stage 5. There was increased ADMA along with increased tHcy concentration of around 20μ mol/L, and this then decreased. The inverse correlation between tHcy and ADMA concentrations started to appear in CKD stage 4, but this correlation was statistically insignificant (r2 =0.19; p=0.499).CONCLUSIONS: This study showed there was a correlation between homocysteine and ADMA concentrations in patients with CKD stage 2 to 5, although statistically not significant.KEYWORDS: Asymetric Dimethylarginine, Homocysteine, Chronic Kidney Disease